Слово авторитета: роман / Евгений Сухов - Сухов Евгений Евгеньевич (ЭКСМО-Пресс, 2001)
Экземпляры: Камская библиотека (20181203) / Инвентарный номер: 5538 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 91 / ББК: 84(2Рос=Рус)6